Bioequivalence of Different Prednisolone Tablet Formulations - Luippold, Gerd; Benöhr, Peter; Schneider, Swetlana; Marto, Maria; Mühlbauer, Bernd (Arzneimittelforschung, 2001)
The relative bioavailability of different prednisolone (CAS 50-24-8) tablet formulations (Prednisolon Ferring 2, 5, and 20 mg) was investigated in comparison to a reference formulation. The study was performed in a GCP/ICH-conform manner using a randomized cross-over design in 13 healthy volunteers. With respect to the pharmacokinetic parameters Cmax (maximal prednisolone concentration), AUC0 -12 h (area under the concentration-time curve until 12 h after drug intake), AUC0–∞ (area under the concentration-time curve until infinity), and t1/2 (elimination half-life time), 10 × 2 mg prednisolone tablets did not show any relevant differences as compared to the reference (1 × 20 mg) meaning that the 90 % confidence intervals were within the given 0.80-1.25 limits for the decision of bioequivalence. Although not statistically significant, tmax (time to reach the maximal prednisolone plasma concentration) was 11 min shorter regarding the test preparation as compared to the reference. The pharmacokinetic parameters of 4 × 5 prednisolone tablets were also well in accordance with the reference. The most important parameters Cmax, AUC and t1/2 were within the defined limits for the acceptance of bioequivalence and, in addition, tmax did not show any significant differences. The 20 mg prednisolone tablet formulation showed almost identical parameters of Cmax, AUC, t1/2 und tmax in comparison to the reference substance. Taken together, the results of the bioavailability parameters indicate the bioequivalence of the three prednisolone test preparations as compared to the reference.
Keywords: CAS 50-24-8; Prednisolone, bioequivalence, clinical studies; Prednisolon Ferring